2015
DOI: 10.1164/rccm.201503-0529oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Heart Failure. Epidemiology, Right Ventricular Function, and Survival

Abstract: Cpc-PH is rare in chronic heart failure. Right ventricular-pulmonary vascular coupling is poor in Cpc-PH and could be one explanation for dismal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
240
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(258 citation statements)
references
References 40 publications
13
240
2
3
Order By: Relevance
“…The exact definition of PH in the setting of left heart disease is still debated, but includes at least the criteria of a mean pulmonary artery pressure greater than or equal to 25 mmHg and a pulmonary capillary wedge pressure greater than or equal to 15 mmHg (10). Additional hemodynamic criteria of PH in the setting of left heart disease, along with how such criteria affect prevalence and outcomes, continue to be debated, with the ultimate goal to identify a phenotype amenable to specific targeted therapies (1,2,(10)(11)(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…The exact definition of PH in the setting of left heart disease is still debated, but includes at least the criteria of a mean pulmonary artery pressure greater than or equal to 25 mmHg and a pulmonary capillary wedge pressure greater than or equal to 15 mmHg (10). Additional hemodynamic criteria of PH in the setting of left heart disease, along with how such criteria affect prevalence and outcomes, continue to be debated, with the ultimate goal to identify a phenotype amenable to specific targeted therapies (1,2,(10)(11)(12)(13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…This difference is not trivial. GERGES and co-workers [5,6] had previously shown that Cpc-PH as a complication of heart failure with or without preserved ejection fraction, or increased risk of pulmonary vascular disease in these patients is associated with more severe PH, worse functional class, more commonly altered right ventricular function and decreased survival, when compared with Ipc-PH.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…This difference is not trivial. GERGES and co-workers [5,6] had previously shown that Cpc-PH as a complication of heart failure with or without preserved ejection fraction, or increased risk of pulmonary vascular disease in these patients is associated with more severe PH, worse functional class, more commonly altered right ventricular function and decreased survival, when compared with Ipc-PH.The debate about the best combination of measurements to predict morphological changes in the pulmonary circulation is not new. When COURNAND et al [7] reported in 1945 the first cardiac catheterisation of a patient, who happened to suffer from severe PH on mitral stenosis, the histopathology of this form of PH-LHD had already been extensively described [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated post‐capillary PH (Ipc‐PH) represents a unique subset of those with PH and can be defined by a diastolic pulmonary gradient (DPG) <7 mmHg, while combined pre‐capillary and post‐capillary PH (Cpc‐PH) patients have a DPG ≥7 mmHg 3. More importantly, Cpc‐PH patients not only develop maladaptive pulmonary vascular remodelling but also have poorer right ventricular–pulmonary vascular coupling and worse clinical outcomes 1, 5, 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%